Kain Tenun Baduy: Simbol Komunikasi Pariwisata Berbasis Kearifan Lokal - Noerma Kurnia Fajarwati; Eka Susilawati; Rizqi Fitrianti (Batara Wisnu : Indonesian Journal of Community Services, 2022)
Baduy is one of the tribes located in the administrative area of ??Lebak Regency, Banten Province. The Baduy community is unique in terms of culture and ancestral values ??which upholds simplicity in every life. This community service activity is carried out by Bina Bangsa University in the context of the Tridharma of Higher Education and is a proof of the academic community's concern for the development of tourism communication. Baduy woven cloth is one of the local wisdom heritages of Baduy culture and the main product that makes Baduy known to outsiders